Theoretical value of investment process (Путеводитель предпринимателя, 2020)
Traditionally at the heart of economy growth investments into fixed capital, i.e. directed on development of technologies and innovations during too time have defining value, it is necessary to consider influence of behavior of investors and the risks accompanying investment process that, finally, defines its efficiency.